Somatic mutation profiling of hobnail variant of papillary thyroid carcinoma. Issue 2 (February 2017) - Morandi, Luca; Righi, Alberto; Maletta, Francesca; Rucci, Paola; Pagni, Fabio; Gallo, Marco; Rossi, Sabrina; Caporali, Leonardo; Sapino, Anna; Lloyd, Ricardo V; Asioli, Sofia
Abstract : Hobnail variant of papillary thyroid carcinoma (HPTC) represents a recently described, aggressive and rare group of thyroid tumors with poorly understood pathogenesis. Molecular data about this group of cancers are few, and a more detailed molecular characterization of these tumors is needed. The main objective of the study is to define a comprehensive molecular typing of HPTC. Eighteen patients affected by HPTC, including eighteen primary tumors and four lymph node metastases, were screened for NRAS, KRAS, HRAS, BRAF, TP53, PIK3CA, hTERT, PTEN, CDKN2A, EGFR, AKT1, CTNNB1 and NOTCH1 gene mutations. Sequencing is conducted on the MiSEQ system, and molecular data are compared with clinical-pathologic data and follow-up. The patients include 14 women and 4 men. Ages range from 23 to 87 years. All 18 primary tumors of HPTC showed ≥30% hobnail features. BRAF and TP53 mutations are by far the most common genetic alterations in primary HPTC (72.2% and 55.6%, respectively), followed by hTERT (44.4%), PIK3CA (27.8%), CTNNB1 (16.7%), EGFR (11.1%), AKT1 (5.5%) and NOTCH1 (5.5%). The mutational pattern in primary tumors and metastasis was usually maintained. Univariate Cox regression analyses with bootstrap procedure indicated a significantly increased mortality risk in patients harboring BRAF mutation and BRAF mutation associated with TP53 and/or PIK3CA mutations. The detection of these multiple mutations appears to allow the identification of a subset of more aggressive tumors within the group and to bear information that should be useful for prognostic stratification of these patients including the planning of adjuvant therapy.